Factors That Influence On Village Financial Management - Dwi Astarani Aslindar (Jurnal Ekonomika dan Bisnis, 2022)
This study aims to examine the effect of accountability, transparency, community participation, quality of human resources, and supervision on village financial management. This research is a quantitative study and the sample in this study was obtained using the proportional sampling method, namely 12 villages in the Plantungan Kendal district. This study took data from 60 respondents using the proportional sampling method. The analytical method used is multiple linear analysis with SPSS 23 application tools. The results of the research test show that accountability, transparency and community participation have no effect on village financial management. Other results show that the quality of human resources and supervision has an effect on village financial management. Theoretically, the research results provide additional knowledge and become a reference in the development of further research. While practically this research contributes to the village government in managing village finances so that they can organize government by applying the principles of transparency and accountability.